The critical equation of state of the two-dimensional Ising model - Caselle, M.; Hasenbusch, Martin; Pelissetto, Andrea; Vicari, Ettore (Journal of physics. A, Mathematical and general, 2001)
We compute the 2n-point coupling constants in the high-temperature phase of the two-dimensional Ising model by using transfer-matrix techniques. This provides the first few terms of the expansion of the effective potential (Helmholtz free energy) and of the equation of state in terms of the renormalized magnetization. By means of a suitable parametric representation, we determine an analytic extension of these expansions, providing the equation of state in the whole critical region in the t,h plane.
Gesehen am 08.07.2022